2007
DOI: 10.5897/ajb2007.000-2391
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and functional properties of flour produced from two varieties of tigernut (Cyperus esculentus)

Abstract: The chemical composition and functional properties of flour produced from two varieties (yellow and brown) of tigernut (Cyperus esculentus) seeds were studied. The seeds were obtained in dried form, sorted, wet cleaned, dried, milled and sieved to produce flour. The flours were tagged YTF and BTF for yellow and brown varieties, respectively. The protein contents of YTF and BTF were 7.15 and 9.70%, respectively. BTF has higher fat, ash, potassium, magnesium, manganese and iron contents than YTF. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
201
13
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(240 citation statements)
references
References 19 publications
24
201
13
2
Order By: Relevance
“…The lowest swelling power was recorded for cowpea flour while the highest one was observed for the composite cowpea-sweet potato (50-50%) flour. However, the swelling (2.47; 2.10) powers reported by Oladele & Aina [22] for tigernut flours were higher than those obtained in this study. In addition, relative high swelling powers values (2.65 to 2.68) were reported by Appiah et al [3] for some cowpea flours grew in Ghana.…”
Section: Swelling Powercontrasting
confidence: 55%
“…The lowest swelling power was recorded for cowpea flour while the highest one was observed for the composite cowpea-sweet potato (50-50%) flour. However, the swelling (2.47; 2.10) powers reported by Oladele & Aina [22] for tigernut flours were higher than those obtained in this study. In addition, relative high swelling powers values (2.65 to 2.68) were reported by Appiah et al [3] for some cowpea flours grew in Ghana.…”
Section: Swelling Powercontrasting
confidence: 55%
“…The crude protein concentration is similar to the range 12%-13.73% recorded for plantain peel meal [13,14] but higher than the value of 10% for maize [15] and 7%-9.7% for tigernut [16]. The value (12.39%) of crude fibre in kunnu waste/chaff that is slightly above the value of (9%-10%) recorded for composite ingredients of sorghum and maize used for the kunnu [16] is attributed to the action of microbes of [17,18]. All the kunnu chaff based diets recorded higher but no significant crude protein concentration (p .…”
Section: Resultsmentioning
confidence: 49%
“…Concerning amino acids composition, tiger nut is rich in glutamic acid, methionine, arginine and aspartic acid. Its mineral composition revealed high amounts of potassium, phosphorous, sodium, calcium, and magnesium (Ekcanyanwu and Ononogbu, 2010;Glew et al, 2006;Oladele and Aina, 2007). According to Chukwuma et al (2010), several groups of phytochemicals are present in tiger nut, with marked differences between raw and roasted ones.…”
Section: Introductionmentioning
confidence: 99%
“…The compositional study of tiger nut revealed that they possess low amounts of water, but are rich in fat, fibres, and carbohydrates, being a good source of starch (Arafat et al, 2009;Coş kuner et al, 2002;Ekcanyanwu and Ononogbu, 2010;Oladele and Aina, 2007;Ozcan et al, 2010). Concerning fat composition, tiger nut oils are predominantly monounsaturated, being a good source of essential fatty acids that the human organisms cannot synthesize (Kim et al, 2007;Sánchez-Zapata et al, 2012a;Yeboah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation